Substitution.

Slides:



Advertisements
Similar presentations
Introduction to Theorem Proving
Advertisements

Inference and Reasoning. Basic Idea Given a set of statements, does a new statement logically follow from this. For example If an animal has wings and.
1 Section 1.7 Set Operations. 2 Union The union of 2 sets A and B is the set containing elements found either in A, or in B, or in both The denotation.
Chapter 9: Boolean Algebra
EE1J2 – Discrete Maths Lecture 5
Proof by Deduction. Deductions and Formal Proofs A deduction is a sequence of logic statements, each of which is known or assumed to be true A formal.
Series-Parallel Combination Circuits
Copyright © Curt Hill Truth Tables A way to show Boolean Operations.
Deduction, Proofs, and Inference Rules. Let’s Review What we Know Take a look at your handout and see if you have any questions You should know how to.
Thinking Mathematically
Foundations of Discrete Mathematics Chapter 1 By Dr. Dalia M. Gil, Ph.D.
Introduction to Logic © 2008 Pearson Addison-Wesley.
Chapter 1 Logic and Proof.
Logic.
Chapter 2 Sets and Functions.
2. The Logic of Compound Statements Summary
Lecture 1.2: Equivalences, and Predicate Logic
Propositional Logic.
The Foundations: Logic and Proofs
AND.
Lesson Objectives Aims Be able to define problems using Boolean logic
Lecture 1 – Formal Logic.
Thinking Mathematically
Truth Tables and Equivalent Statements
Chapter 1 – Logic and Proof
CHAPTER 3 Logic.
COMP 1380 Discrete Structures I Thompson Rivers University
7/20/2018 EMR 17 Logical Reasoning Lecture 7.
Discussion #10 Logical Equivalences
Mathematics for Computing
Jeremy R. Johnson Wed. Sept. 29, 1999
A v B ~ A B > C ~C B > (C . P) B / ~ B mt 1,2 / B ds 1,2
Jeremy R. Johnson Anatole D. Ruslanov William M. Mongan
Information Technology Department
Chapter 14 Probability Rules!.
CS 220: Discrete Structures and their Applications
CS201: Data Structures and Discrete Mathematics I
Everything you need to know
Truth Trees.
Fundamentals of Computer Systems
Propositional Equivalences
Propositional Logic.
The Chain Rule Theorem Chain Rule
Chapter 3 Introduction to Logic 2012 Pearson Education, Inc.
Lecture 2: Propositional Equivalences
L5 Set Operations.
Chapter 15 Probability Rules!.
ECE 352 Digital System Fundamentals
Equivalent Statements
Predicates and Quantifiers
Foundations of Discrete Mathematics
COMP 1380 Discrete Structures I Thompson Rivers University
The Five-Paragraph Essay
CS201: Data Structures and Discrete Mathematics I
ECE 352 Digital System Fundamentals
ECE 352 Digital System Fundamentals
Compounding.
Chapter 8 Natural Deduction
Doing Derivation.
Introducing Natural Deduction
CHAPTER 3 Logic.
Validity and Soundness, Again
Logical truths, contradictions and disjunctive normal form
The Main Connective (Again)
Starting out with formal logic
Truth tables.
More Derived Rules.
Logical equivalence.
Subderivations.
The conditional and the bi-conditional
Presentation transcript:

Substitution

Substituting logical equivalents The law of double negation tells us that A and ~~A are equivalent. So, it seems pretty clear that A ∧ B and ~~A ∧ B are also equivalent. Why? Because the only way that the components of compound sentences effect those compound sentences is through their truth- values. So if you switch one component with another that has exactly the same truth-values in all cases, you won’t effect the compound sentence’s truth valuations at all.

The law of substitution of logical equivalents This important insight gives us the law of substitution of logical equivalents (or SLE) for short. SLE: Suppose that X and Y are logically equivalent, and suppose that X occurs as a sub-sentence or component of some larger sentence Z. Let Z* be the new sentence obtained by substituting Y for X in Z. Then Z is logically equivalent to Z*.

Proving equivalence using the laws Now that we have SLE, and the laws of logical equivalence that we discussed in the previous session, we have enough for a new method of showing logical equivalence. (This is pretty useful, because though truth tables and Venn diagrams are illustrative for simple examples, once we start dealing with longer sentences of sentence logic they become wildly impractical.)

Proving equivalence using the laws The idea is fairly simple at heart, but it’s important to get it right. Those laws we reviewed last session give us some general rules for what sorts of sentences are logically equivalent to each other. (E.g. the law of double negation tells us that anything of the form ~~X, where X is just any sentence of sentence logic, is logically equivalent to X.)

Proving equivalence using the laws And then the law of substitution of logical equivalents tells us that we can substitute any component of a compound sentence with a logical equivalent to that component and end up with something that is logically equivalent to the original compound sentence. So we can apply these laws together to show that two different sentences of sentence logic are logically equivalent.

An example Let’s look at an example. Let’s prove that ~(~P ∧ Q) is logically equivalent to P ∨ ~Q We start with ~(~P ∧ Q). We’re going to have to get from this disjunction to a conjunction. And that’s just what those De Morgan Laws we proved last session can help us to do. Let’s look back at those laws.

An example One of those laws says that ~(X ∧ Y) is logically equivalent to ~X ∨ ~Y. The sentence we are starting with is ~(~P ∧ Q). But this is just an instance of ~(X ∧ Y), with ~P as X and Q as Y. So De Morgan’s Law tells us that ~(~P ∧ Q) is logically equivalent to ~~P ∨ ~Q. We’re close to our final destination of P ∨ ~Q now.

An example We just need to turn that ~~P into a P. But that’s easy! Because the law of double negation tells us that ~~P is logically equivalent to P. And the law of substitution of logical equivalents tells us that we can therefore substitute our ~~P for a P and end up with a logically equivalent sentence. So ~~P ∨ ~Q is logically equivalent to P ∨ ~Q.

An example So now we have shown that ~(~P ∧ Q) is logically equivalent to ~~P ∨ ~Q and that ~~P ∨ Q is logically equivalent to P ∨ ~Q. So we can (because of a law we will introduce shortly) conclude that ~(~P ∧ Q) is logically equivalent to P ∨ ~Q .

An example The standard way of writing such a proof is like this: ~(~P ∧ Q) ~~P ∨ ~Q DM P ∨ ~Q DN, SLE

Some more laws A couple of slides back I said that because we had proved that ~(~P ∧ Q) is logically equivalent to ~~P ∨ ~Q and that ~~P ∨ Q is logically equivalent to P ∨ ~Q, we could conclude that ~(~P ∧ Q) is logically equivalent to P ∨ ~Q. This is because of the law of transitivity of logical equivalents, which just says that for any three sentences X, Y and Z, if X is logically equivalent to Y and Y is logically equivalent to Z, then X is logically equivalent to Z.

More laws Like the law of transitivity of logical equivalents, these laws are pretty intuitive – but they’re important! Don’t worry if they seem perplexing to you now, once you get the hang of proofs you’ll start to see the rationale for them. The commutative law: for any sentences X and Y, X ∧ Y is logically equivalent to Y ∧ X. And X ∨ Y is logically equivalent to Y ∨ X.

More laws The associative law: For any sentences X, Y, and Z, X ∧ (Y ∧ Z), (X ∧ Y) ∧ Z and X ∧ Y ∧ Z are logically equivalent to each other. And X ∨ (Y ∨ Z), (X ∨ Y) ∨ Z and X ∨ Y ∨ Z are logically equivalent to each other. (Similarly, conjunctions with four or more components may be arbitrarily grouped and similarly for disjunctions with four or more disjuncts.)

More laws The law of redundancy: for any sentence X, X ∧ X is logically equivalent to X. Likewise, X ∨ X is logically equivalent to X.

Getting the hang of it This all might seem a little confusing. Don’t panic – seeing all these laws at once is a confusing experience. The best way to understand them is just to jump in and start doing examples. Go through Teller’s exercises in the text if you need to – this will help a lot. The more you practice, the easier it will get.

Examples Let’s do some examples together on the board now. ‘~~A ∨ B’ is logically equivalent to ‘B ∨ A’ ‘X ∧ (~~Y ∨ Z)’ is logically equivalent to ‘(X ∧ Z) ∨ (X ∧ Y)’